Behavior of Enzyme Activity of Gamma Glutamyl Transferase in Bovine Ruminal Liquid Subjected to Thermal, Physical and Chemical Treatments - Cuervo, Wilmer A.; Correa, Héctor J. (Spei Domus, 2012)
In order to determine the effect of treatments using centrifugation, thawing and the addition of magnesium salts on activity in rumen fluid (LR) of gamma glutamyl transferase (GGT) cattle, 2 samples (100 mL each) of LR were extracted from mature, fistulated Holstein cows (620 ± 14 Kg 7 years old). Samples were stored frozen and then divided equally and subjected to sequential treatments of thawing [room temperature (LRDC) or water bath (LRCal)], centrifugation [9.000 rpm x 10 min (LRDC+C and LRCal+C)], and the addition of salt and Mg [MgSO4 or MgCl2]. The data were compared with fresh rumen fluid (LRF) extracted from the same cows. The activity of the gamma glutamil transferase (GGT) was measured on all samples by applying the colorimetric method using a spectrophotometric kit (Biosystems®). The means of treatments were compared using a t test, which revealed that samples of lr with the addition of MgCl2 had significantly greater in vitro activity (p < 0.01) than samples from the control group or from those treated with MgSO4. A decrease in enzyme activity was also observed when the samples were placed in a centrifuge, as compared to other treatments. We conclude that the Mg++ positively affects GGT enzyme activity in vitro in contrast to the physical effect of the spin treatment. Although both thermal treatments increased enzyme activity, there were no significant differences with respect to fresh rumen fluid.
Keywords: aminotransferases; divalent ions; non-protein nitrogen; rumen; dairy cows